G protein coupled receptor kinase-2 upregulation causes κ-opioid receptor desensitization in diabetic heart - Chen, Xiyao; Zhao, Shihao; Xia, Yunlong; Xiong, Zhenyu; Li, Yueyang; Tao, Ling; Zhang, Fuyang; Wang, Xiaoming (Biochemical and biophysical research communications, 2017)
Activation of κ-opioid receptor (KOR) ameliorates myocardial ischemia/reperfusion (I/R) injury; however, cardioprotective effects of KOR stimulation disappear in type 1 diabetic subjects with hyperglycemia. The molecular mechanisms underlying this phenomenon remain unknown. Here we found that KOR expression was obviously downregulated and KOR agonism-induced contractile-regulatory and cardioprotective effects were significantly impaired in hearts isolated from streptozotocin (STZ) injection-induced diabetic mice. These in vivo data identified cardiac KOR desensitization as a novel characteristic of the diabetic heart. In cultured cardiomyocytes, high glucose (HG) caused obvious KOR downregulation, accompanied by an upregulation of G protein coupled receptor kinase-2 (GRK2). We found that HG exposure increased the interaction between GRK2 and KOR. More importantly, HG-induced KOR downregulation was reversed by small interfering RNA (siRNA)-mediated GRK2 inhibition. GRK2 knockdown also restored KOR agonism-mediated protection against simulated I/R injury in cardiomyocytes. These in vitro data revealed an essential role of GRK2 in HG-induced KOR desensitization. Finally, cardiac-specific GRK2 knockdown by intramyocardial siRNA injection blocked KOR downregulation and restored contractile-regulatory and cardioprotective effects of KOR agonism in hearts of diabetic mice. In conclusion, these data for the first time demonstrate that GRK2 upregulation is largely responsible for cardiac KOR desensitization in diabetic individuals, which provides novel insights into the management of myocardial I/R injury in patients with diabetes. •In type 1 diabetic mice, KOR is desensitized in the heart.•Upregulation of GRK2 plays an essential role in cardiac KOR desensitization in diabetic mice.•Inhibition of GRK2 is a novel and effective strategy to restore cardiac KOR sensitivity.